Exploring the relationship between peatland net carbon balance and apparent carbon accumulation rate at century to millennial time scales - Frolking, S.; Talbot, J; Subin, Z.M. (SAGE Publications, 2014)
Each year, a peatland has an annual net carbon balance ( NCB), which can be positive (net uptake), zero or negative. Over centuries to millennia, this NCB accumulates as a peat profile. Contemporary peatlands can be sampled (cored), and the past apparent carbon accumulation rate ( aCAR) can be determined as the quantity of peat carbon in any particular dated interval down the core profile. We use a process-based peatland carbon and water cycle model to compare peatland annual NCB during millennia of peat accumulation to the contemporary estimate of aCAR, resulting from this accumulation. Integrating over the entire profile, the accumulated NCB must equal the aCAR, but for shorter time intervals, these two quantities can diverge. A climate variation/perturbation that leads to persistent, slow carbon loss or negligible carbon gain through enhanced decomposition will necessarily reduce the aCAR for time periods before the climate variation/perturbation occurred. This can compromise peatland climate–carbon balance relationships inferred from joint analysis of peat cores and paleoclimate reconstructions.